Gradation of Actors, Interplay of Roles, Range of Cooperation, and Composition in Embeddedness: Complementary Ideas for Strategic Action Field Theory - Alamsyah, Andi Rahman (Masyarakat: Jurnal Sosiologi, 2022)
Classical debates in sociology or social science tend to gravitate around what determines the formation of social phenomena: actors or structures and ideas or matter. These debates have spawned various theories that emphasize on actors or structures, ideas or material forces, as well as various combinations of all four. One such combination is reflected in Fligstein and McAdam’s theory of the Strategic Action Field (SAF). According to them, social phenomena are formed through SAFs (at the meso-level), which becomes an arena for collaboration and conflict between actors (at the micro-level) with their respective social skills, including instrumental and existential factors. These strategic action fields, on the other hand, are also embedded to and influenced by other SAF (forming the macro-level structure). While I agree with this theory, I also found several gaps within it: the dichotomy between incumbent versus challenger actors; ignorance of the possibility of a “tug-of-war” between existential and instrumental factors; the nature of collaboration between actors; as well as the particular composition of aspects and sub-aspects in embeddedness. To overcome these theoretical shortcomings, I offer four ideas: actors within a SAF occupy positions in a gradational sense; an outline of the interplay between existential and instrumental factors; the effect of three modes of social capital, namely bonding, bridging, and linking, to SAF dynamics; and two types of composition in SAF embeddedness.